2010
DOI: 10.1039/c0an00098a
|View full text |Cite
|
Sign up to set email alerts
|

The potential of backscattering interferometry as an in vitro clinical diagnostic tool for the serological diagnosis of infectious disease

Abstract: Backscattering interferometry enables the detection of syphilis antibody–antigen interactions in the presence of human serum, showing promise as a diagnostic tool for the serological diagnosis of infectious disease with potentially quantitative capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…BI can detect both free solution or surface immobilized molecular interactions with unprecedented limits in microfluidic devices (picoliter detection volume) and allows real-time determination of binding constants spanning from micro-to picomole. Kussrow et al have shown the potential of utilizing BI for rapid detection of purified total human IgG from seropositive syphilis patients using a purified recombinant treponenmal antigen r17, demonstrating the prospect of using this approach for serological diagnosis in clinical samples [26].…”
Section: Optical Transducermentioning
confidence: 99%
“…BI can detect both free solution or surface immobilized molecular interactions with unprecedented limits in microfluidic devices (picoliter detection volume) and allows real-time determination of binding constants spanning from micro-to picomole. Kussrow et al have shown the potential of utilizing BI for rapid detection of purified total human IgG from seropositive syphilis patients using a purified recombinant treponenmal antigen r17, demonstrating the prospect of using this approach for serological diagnosis in clinical samples [26].…”
Section: Optical Transducermentioning
confidence: 99%
“…(D) Quantitative measurement of titer strength for syphilis in human sera samples. Ref 108–Reproduced by permission of The Royal Society of Chemistry, Copyright 2010. (E) Binding of trinitrophenol to its antibody using an end point assay.…”
Section: Figurementioning
confidence: 99%
“…End‐point assays were performed similarly to those recently described by our group 15. In short, the changes in RI arising from binding with CAII were measured for a series of inhibitor concentrations, allowing the determination of K D for the interaction.…”
Section: Concentrations Of Caii and Inhibitor Used On Each Analysis Wmentioning
confidence: 99%
“…Creating a separate DMSO calibration to subtract the bulk effects of DMSO alone is unnecessary with BSI, eliminating preparation error that could be present in other methodologies. BSI not only allows binding partners to remain in their native state without potentially perturbing labels or immobilizations, but also more easily accommodates assays that require DMSO, complex matrices 15 or other high‐RI additives. Finally, BSI is not a mass‐sensitive sensor making it compatible with a wide range of solutes and targets including small molecule–protein interactions, protein–DNA or small molecule–DNA interactions and large protein complex–inhibitor interactions.…”
Section: Concentrations Of Caii and Inhibitor Used On Each Analysis Wmentioning
confidence: 99%